PENERTIBAN HEWAN TERNAK DI KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Panungkul, M. Arif (Katalogis, 2015)
This Research Target is know and analyse the implementation of Publisher of Livestock Animal specially ox and goat in Donggala Regency Province Of Central Sulawesi is which relate at Legal theory of System Theory of according to Lawrence M. Friedman that is: (1) Structure legal (2) Subtansi legalÂ  and (3) Culture legal the. this Research Type is research qualitative with the informan selected by the four of people. Data collecting use the technique interview and documentation. Technique of Substance Gathering Punish composed by the Substance punish the primary, covering relevant Regulation with this research like: Constitution of State of Republic Of Indonesia of Year 1945, Number /Law 23 Year 2014 about Area Governance, Number Law 18 Year 2008 about Management of Garbage of Number Law 10 Year 2009 about Keparawisataan of Number Code/Law 18 Year 2009 about Ranch And Animal Health, Number Law 32 Year 2009 about Protection and Environment Management, Governmental Regulation of Number 27 Year 1999 about Analysis of Concerning Environmental Impact. By Law of Regency of Donggala Number 14 Year 2010 About Ranch and its Publisher. As for substance of legal secunder that is hand in glove law substance of relation/link with the law and can assist to analyse and comprehend the substance punish the primary. Result of research is livestock animal curbing in Regency Donggala not yet walked better. This matter is happened by because society behavior do not always in line with existing norm in code/law. Its cause is very immeasurable one among other things is that norm do not in line with society orientation. Practically, law conception having the character of national is easy to accepted by society especially which is concerning economic social need, but which is concerning culture of how society represent the sensitive problem in society